Cot B / sec B - tan B - cos B / sec B + tan B = sin B + csc B ?

1 Answer
Mar 13, 2018

Verified below

Explanation:

cotB/(secB-tanB)-cosB/(secB+tanB)= sinB+cscBcotBsecBtanBcosBsecB+tanB=sinB+cscB

A common denominator to add these fractions:
(cotB(secB+tanB))/((secB-tanB)(secB+tanB))-(cosB(secB-tanB))/((secB+tanB)(secB-tanB))= sinB+cscBcotB(secB+tanB)(secBtanB)(secB+tanB)cosB(secBtanB)(secB+tanB)(secBtanB)=sinB+cscB
(cotB*secB+cotB*tanB)/(sec^2B-tan^2B)-(cosB*secB-cosB*tanB)/(sec^2B-tan^2B)cotBsecB+cotBtanBsec2Btan2BcosBsecBcosBtanBsec2Btan2B

Before we combine let's apply one Pythagorean identity:
1+tan^2x=sec^2x1+tan2x=sec2x
Manipulated to:
1=sec^2x-tan^2x1=sec2xtan2x
That should look familiar as sec^2x-tan^2xsec2xtan2x is our denominator, so let's substitute a 1 in there:
(cotB*secB+cotB*tanB)/(1)-(cosB*secB-cosB*tanB)/( 1)cotBsecB+cotBtanB1cosBsecBcosBtanB1

There's still one more step before we combine, we need to utilize reciprocal and quotient identities to make the expression simpler:
tanx= sinx/cosxtanx=sinxcosx
cotx= 1/tanxcotx=1tanx
secx= 1/cosxsecx=1cosx
cotx= cosx/sinxcotx=cosxsinx
1/sinx= cscx1sinx=cscx

So:
(cancel(cosB)/sinB*1/cancel(cosB)+1/cancel(tanB)*cancel(tanB))/(1)-(cancel(cosB)*1/cancel(cosB)-cancel(cosB)*sinB/cancel(cosB))/( 1)

Leaves us with:
cscB+1-(1-sinB)

Distribute the negative:
cscBcancel(+1)cancel(-1)+sinB

Gets us to:
sinB+cscB

In case confusion is caused from where cscB came from: remember: 1/sinx= cscx